Hacia un estudio multidisciplinar del proceso de globalización - Ravier, Adrián Osvaldo Ravier (REVISTA PROCESOS DE MERCADO, 2009)
The objective of this article is to study the process of globalization from a multidisciplinary perspective. First, through a historical and evolutionary focus, where we will observe that the globalization is an institution originated in the spontaneous order, just as they are also the division of labor, the price system, the money, the law or the language. Second, through the economic analysis, where we confront the «free trade» —that, through the elimination of barriers, results in the dynamic entrepreneur creativity— versus what Gabriel Zanotti named as the «globalization of the interventionism» —where the government tries to plan and control everything, always generating results that are just the opposite to those it looked for—. Third, we develop a legal and institutional research, analyzing the advantages of the arbitration and the non legal sanctions, as a complement of the public enforcement. Finally, we go into the implications that the globalization exercises on the culture, criticizing the nationalism and the «fenced culture», to give place to an open and «cosmopolitan» society. Key words: Globalization process. Multidisciplinary study. Spontaneous order. Interventionism. Myths of the international trade. Arbitration. Lex Mercatoria. Enforcement. Nationalism. Fenced culture. Austrian School of Economics. JEL codes: B25, B53, E32, E44, F02. Resumen: El objetivo de este artículo es estudiar el proceso de globalización desde una perspectiva multidisciplinar. Primero, a través de un enfoque histórico y evolutivo, donde observaremos que la globalización es una institución originada en el orden espontáneo, tal como lo son también la división del trabajo, el sistema de precios, la moneda, el derecho o el lenguaje. Se-gundo, a través del análisis económico, donde confrontamos la «libertad de comercio» —que, a través de la eliminación de barreras, da lugar a la dinámica creatividad empresarial— versus lo que Gabriel Zanotti denominó como la «globalización del intervencionismo» —donde el Estado todo lo intenta planificar y controlar, generando siempre resultados contrarios a los buscados—. Tercero, desarrollamos una investigación jurídico-institucional, analizando las ventajas del arbitraje y las sanciones no legales, como complemento del enforcement público. Finalmente, nos adentramos en las implicaciones que la globalización ejerce sobre la cultura, criticando el na-cionalismo y la «cultura alambrada», para dar lugar a una sociedad abierta y «cosmopolita». Palabras clave: Proceso de globalización. Estudio multidisciplinar. Orden espontáneo. Intervencionismo. Mitos del comercio internacional. Arbitraje. Lex Mercatoria. Enforcement. Nacionalismo. Cultura alambrada. Escuela Austriaca de Economía. Códigos JEL: B25, B53, E32, E44, F02.